Carbon Pricing Without the Tax: Investment Behavior Under Emerging Market Signals in Indonesia - Kasno; Nurlaela, Lina (Summa : Journal of Accounting and Tax, 2025)
Indonesia has adopted a hybrid carbon pricing strategy, combining a postponed carbon tax with operational instruments such as the Emissions Trading System (ETS) and the IDXCarbon exchange. This study examines whether these early pricing signals have already shaped firm-level investment behavior before the formal enforcement of the carbon tax. The methodology incorporates firm level variables such as ETS exposure, carbon intensity, and export dependence on the EU Carbon Border Adjustment Mechanism (CBAM), while controlling for financial indicators like profitability, size, and leverage. Key results indicate that firms with higher exposure to ETS and CBAM related markets significantly increased their environmental CapEx during the observed period. Event analysis reveals marked investment shifts following the launch of IDXCarbon and the government's carbon tax announcements. These findings suggest that Indonesian firms are responsive to carbon pricing signals even before full regulatory enforcement, especially when those signals are perceived as credible and market relevant. However, policy delays and uncertainty have moderated the pace and scale of investment responses. The discussion highlights the importance of internal carbon pricing, sectoral heterogeneity, governance dynamics, and comparisons with early phase ETS experiences in the EU, China, and Korea. The study concludes that clear and credible carbon pricing frameworks are essential for mobilizing private sector investment in sustainability. Indonesia must enhance the regulatory predictability and institutional strength of its carbon pricing system to fully realize its climate and investment objectives.